دور تكنولوجيا الاتصال في تحسين الخدمة بالمؤسسة الخدماتية دراسة ميدانية بمديرية اتصالات الجزائر سوق اهراس - حمدي هناء (My University, 2019)
Abstract: It is recognized that the performance of employees in any institution depends primarily on several factors that help it improve and achieve its objectives. These include modern communication and service technologies, which have created a dynamic communication climate that allows for understanding, interaction, and convergence of viewpoints to achieve the objectives set by institutions, demonstrating its importance in the life of the institution. This study aims to explain the contribution of modern communication technologies and their role in improving the performance of service organizations. The role played by communication technologies in the lives of individuals and communities has made them an integral part of the infrastructure of many institutions that wish to keep abreast of modern developments and the effectiveness of innovations in change. -------------------------- ملخص: من المسلّم به أن أداء العاملين في أي مؤسسة يعتمد بالدرجة الأولى على عدة عوامل تُسهم في تحسينها وتحقيق أهدافها، منها تقنيات الاتصال والخدمات الحديثة، التي أتاحَت مناخًا اتصاليًا ديناميكيًا يتيح التفاهم والتفاعل وتقارب وجهات النظر لتحقيق الأهداف التي تسعى إليها المؤسسات، مما يُبرز أهميتها في حياة المؤسسة. تهدف هذه الدراسة إلى توضيح مساهمة تقنيات الاتصال الحديثة ودورها في تحسين أداء المؤسسات الخدمية. لقد أصبح دور تقنيات الاتصال في حياة الأفراد والمجتمعات جزءًا لا يتجزأ من البنية التحتية للعديد من المؤسسات التي تسعى لمواكبة التطورات الحديثة وفعالية الابتكارات في التغيير. -------------------------- Résumé: Il est reconnu que la performance des employés de toute institution dépend principalement de plusieurs facteurs qui l’aident à s’améliorer et à atteindre ses objectifs sous la forme de technologies modernes de communication et de service, ce qui a créé un climat de communication dynamique permettant la compréhension, l’interaction et la convergence des points de vue afin d’atteindre les objectifs fixés par Institutions et cela prouve son importance dans la vie de l'institution. Cette étude a pour but d’expliquer l’apport des technologies de communication modernes et son rôle dans l’amélioration des performances de l’organisation de services le rôle joué par les technologies de communication dans la vie des individus et des communautés en a fait une partie intégrante de l’infrastructure de nombreuses institutions qui souhaitent se tenir au courant des développements modernes, Et l'efficacité des innovations dans le changement.
Keywords: تكنولوجيا الاتصال، المؤسسة الخدماتية